Knowledge on Learning Disabilities Among Primary School Teachers of Public Schools in Kathmandu - Sharma, Poojan; KC, Sarswoti (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Introduction: Learning disability (LD) is a group of neurodevelopmental disorder appear during childhood and persists despite normal cognitive abilities, intact sensory abilities, adequate sociocultural stimulation and motivation. As the learning disability is prevalent among children the school teachers have major role in identification of children with learning disabilities and referring them to specific agency. Thus the objective of the study was to assess the knowledge of learning disability among the school teachers. Method: A descriptive cross-sectional study was conducted among the primary school teachers of Kathmandu metropolitan city. The total teachersof 11 public schools were included in the study. The total sample size was 106. The schools were selected randomly and all the teachers from selected were included in the study. The research instrument was developed by the researcher themselves. Self-administered questionnaire was used in data collection. Data was entered into and analyzed using database created in SPSS. Descriptive and inferential statistics was used in analysis. Ethical approval was taken from NEHCO IRC. Results: In overall, more than half of the teachers (53.8%) had adequate knowledge on learning disability. Compared to all sub components of learning disability, highest numbers of teachers (71.7%) had adequate knowledge on types followed by on general information (62.3%) and consequences and prognosis (62.3%). However, the least numbers of teachers (50%) had adequate knowledge on management of learning disability. No any socio-demographic characteristics and work related variables found to be associated with knowledge on learning disability. Conclusion: More than half of the school teachers have adequate knowledge on learning disability. Socio-demographic and work related characteristics of teachers are not associated with the knowledge on learning disability.